The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Human Performance Optimization 2019
DOI: 10.1093/oso/9780190455132.003.0010
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sleep in Human Performance and Well-Being

Abstract: This chapter explores the influence of sleep on human performance and well-being. A general discussion of the role of sleep in humans is followed by a description of the functions of various stages of sleep. The authors explore causal factors of insufficient sleep and inventory known effects of sleep restriction on human performance. They then describe the particular challenges of fatigue and sleep deprivation in military operational environments. The efficacy of fatigue countermeasures and alertness aids comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 130 publications
0
11
0
Order By: Relevance
“…Interestingly, sailors who expressed concerns about the habitability in their berthing compartment tended to sleep more. This finding is not surprising if we consider that, due to workload and operational/training demands, sleep at sea is often split sleep, that is, sleep is accrued in multiple episodes that may not align with the sailor's circadian rhythm (Shattuck et al, 2018, Shattuck et al, 2019. Therefore, sailors who accrue their sleep in more sleep episodes may report worse sleep quality compared to sailors with the same (or even less) daily sleep duration accrued in fewer sleep episodes (Kleitman, 1949;Matsangas & Shattuck, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, sailors who expressed concerns about the habitability in their berthing compartment tended to sleep more. This finding is not surprising if we consider that, due to workload and operational/training demands, sleep at sea is often split sleep, that is, sleep is accrued in multiple episodes that may not align with the sailor's circadian rhythm (Shattuck et al, 2018, Shattuck et al, 2019. Therefore, sailors who accrue their sleep in more sleep episodes may report worse sleep quality compared to sailors with the same (or even less) daily sleep duration accrued in fewer sleep episodes (Kleitman, 1949;Matsangas & Shattuck, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Our focus on berthing compartments, as they are called in the Navy, stems from our studies over the last 15 years. Data collections from more than 30 ships have clearly shown that sleep deprivation, endemic in the naval operational environment, affects crew well-being, mood, and performance (Miller et al, 2012; Shattuck et al, 2019). Sailors are chronically deprived of “normal” sleep along any of three dimensions, that is, duration, timing, and quality of sleep (Shattuck & Matsangas, 2015a, 2015b; Matsangas & Shattuck, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Sleep is foundational to optimal human performance; inadequate sleep results in degraded physical and cognitive performance, increased fatigue levels, poor morale, reduced individual and team resilience, and a myriad of other negative outcomes (Goel, Basner, Rao, & Dinges, 2013;Shattuck, Matsangas, & Dahlman, 2018;Shattuck, Matsangas, Mysliwiec, & Creamer, 2019). Human performance impairments due to chronic sleep loss present considerable risks to personal and group safety, mission success, operational effectiveness, and national security (Good, Brager, Capaldi, & Mysliwiec, 2020;Shattuck et al, 2019). Inadequate or insufficient sleep is a major determinant of fatigue which can impair physical performance, such as speed and strength, and mental performance, such as delayed reaction times and decision making (Jepsen, Zhao, & Van Leeuwen, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…An investigation into three collisions, two of which resulted in 17 fatalities and one grounding involving U.S. Navy warships in 2017, found that sleep-deprivation and fatigue played key roles in the accidents (Department of the Navy, 2017b). Also, the nature of naval maritime operations often requires Sailors to engage in shiftwork (i.e., work outside of the typical daytime working hours of 8 a.m. to 5 p.m.), work long hours, and expose themselves to artificial or natural light during circadian inappropriate times (Shattuck & Matsangas, 2017Shattuck et al, 2018;Shattuck et al, 2019). Restricted sleep opportunities and sleep during biologically misaligned times can impair performance and compromise sound decision making, thereby introducing additional risk to an already inherently dangerous working environment.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are no such directives currently in place to protect sailors from poor dietary patterns of behaviors that may result from their work schedule. The importance of this issue becomes clear if we consider the bidirectional relationship between sleep and diet, and the fact that sleep deprivation and circadian misalignment are endemic in the naval operational environment (Shattuck et al, 2019).…”
Section: Introductionmentioning
confidence: 99%